Multilingualism in semantic dementia: language-dependent lexical retrieval from degraded conceptual representations. Issue 2 (1st February 2021) - Calabria, Marco; Jefferies, Elizabeth; Sala, Isabel; Morenas-Rodríguez, Estrella; Illán-Gala, Ignacio; Montal, Victor; Fortea, Juan; Lleó, Alberto; Costa, Albert
ABSTRACT: Background : Patients with the semantic variant of Primary Progressive Aphasia (svPPA) offer a unique opportunity to study the relationship between lexical retrieval and semantics, as they are characterised by progressive degradation of central semantic representations. However, there are few studies of how lexical retrieval across languages is affected in multilingual speakers. Aims : We examine the impact of conceptual degradation in a trilingual patient (TC) with svPPA, to investigate whether the semantic memory breakdown affects her three languages similarly (English-Catalan-Spanish) in different linguistic tasks. Methods & Procedures : We followed up her performance over one year in several tasks including: (a) naming with or without semantic interference contexts, (b) word translation, (c) word- and sentence-picture matching, (d) associative semantic priming and (e) language switching. Outcomes & Results : There was significant response consistency between languages in the items that were relatively well-known and more semantically degraded, at least in a standard picture naming task. The patient's sentence-to-picture matching did not show progressive deterioration in any language. However, some aspects of lexical retrieval showed language-dependency, as indexed by different patterns of performance in semantically-blocked cyclical naming task across languages. Conclusions : These data suggest that while degradation of central semantic representations affects all languages, this deficit can be amplified or ameliorated by the strength of conceptual to lexical mappings, which varies across languages.